2015
DOI: 10.1016/j.humov.2014.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Postural sway and integration of proprioceptive signals in subjects with LBP

Abstract: Patients with non-specific low back pain (LBP) may use postural control strategies that differ from healthy subjects. To study these possible differences, we measured the amount and structure of postural sway, and the response to muscle vibration in a working cohort of 215 subjects. Subjects were standing on a force plate in bipedal stance. In the first trial the eyes were open, no perturbation applied. In the following 6 trials, vision was occluded and subjects stood under various conditions of vibration/no v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
53
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 51 publications
(72 reference statements)
2
53
2
Order By: Relevance
“…On the other hand, we found that the point estimates did not differ between the groups indicating no clinical difference between the groups. As previous studies have found differences in posture and balance between patients with chronic LBP and healthy controls [ 23 , 24 ], our results showed that that Qinematic™ is not sensitive enough for measuring differences in posture and balance for patients with LBP.…”
Section: Discussioncontrasting
confidence: 52%
“…On the other hand, we found that the point estimates did not differ between the groups indicating no clinical difference between the groups. As previous studies have found differences in posture and balance between patients with chronic LBP and healthy controls [ 23 , 24 ], our results showed that that Qinematic™ is not sensitive enough for measuring differences in posture and balance for patients with LBP.…”
Section: Discussioncontrasting
confidence: 52%
“…The associated effects on the disability and physical scale were also low, which means that our sample was not strongly affected by NSLBP during the investigation. Though, other studies have reported differences between individuals with low pain ratings and healthy controls [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, when using a similar balance task (but in erect posture without manipulating the sensorial systems), Kiers et al [28] showed no significant differences in COP oscillation between those with low back pain (n = 33) as compared to those without pain (n = 182). This demonstrates further that the one-legged stance can be a more sensitive test than other balance conditions, as for example bipedal posture (with or without eyes closed) for assessing postural control responses when musculoskeletal pathology is of concern [15].…”
Section: Discussionmentioning
confidence: 98%
“…A limitation of the present study was that there was no comparison with neuromuscular activation and/or with the influence of vibration [28] to help explain the possible proprioceptive mechanisms for maintaining balance during a one-leg stance with CLBP. However, from the clinical perspective, the new findings reported here contribute to the literature towards improving the process of evaluating balance and intervening in subjects with and without CLBP during rehabilitation programs.…”
Section: Discussionmentioning
confidence: 99%